Assessing the risk of human‐to‐wildlife pathogen transmission for conservation and public health. (22nd March 2022) - Fagre, Anna C.; Cohen, Lily E.; Eskew, Evan A.; Farrell, Max; Glennon, Emma; Joseph, Maxwell B.; Frank, Hannah K.; Ryan, Sadie J.; Carlson, Colin J; Albery, Gregory F.
Abstract: The SARS‐CoV‐2 pandemic has led to increased concern over transmission of pathogens from humans to animals, and its potential to threaten conservation and public health. To assess this threat, we reviewed published evidence of human‐to‐wildlife transmission events, with a focus on how such events could threaten animal and human health. We identified 97 verified examples, involving a wide range of pathogens; however, reported hosts were mostly non‐human primates or large, long‐lived captive animals. Relatively few documented examples resulted in morbidity and mortality, and very few led to maintenance of a human pathogen in a new reservoir or subsequent "secondary spillover" back into humans. We discuss limitations in the literature surrounding these phenomena, including strong evidence of sampling bias towards non‐human primates and human‐proximate mammals and the possibility of systematic bias against reporting human parasites in wildlife, both of which limit our ability to assess the risk of human‐to‐wildlife pathogen transmission. We outline how researchers can collect experimental and observational evidence that will expand our capacity for risk assessment for human‐to‐wildlife pathogen transmission. Abstract : Human‐to‐wildlife pathogen transmission has played an important role in the epidemiology of a number of pathogens in the past, and is likely continuing to play an important role in the Anthropocene. Despite much concern surrounding the transmission of human pathogens into animal populations, particularly during the SARS‐CoV‐2 pandemic, there has been little critical assessment of the evidence base and the threat of these pathogens for conservation and public health. Here, we compile an evidence base of 97 published human‐to‐wildlife pathogen transmission events, and we discuss the sampling biases that have likely played an important role in producing the observed patterns, discussing how to collect further data to aid in risk assessment in the near future.